Utilization of carbohydrate rich ingredients in the feed of Indian major carp, Labeo rohita - Sethuramalingam, T A; Haniffa, M A (Indian Journal of Fisheries, 2011)
The optimum protein and energy (P/ E) ratio and digestibility of eight carbohydrate-rich ingredients in the diets for rohu fingerlings were studied. The formulateddiets contained energy levels of 278, 293, 309 and 334Kcal/100g at low(23%) and 276, 316, 334 kcal/ 100 g at sub-optimum (29-31%) protein levels.Diets containing 23.18% protein and 278 (Kcal/100 g or 28.5% protein and 334Kcal/1 00 g produced better growth and feed conversion than high protein diets.Specific growth rate (SGR), Food conversion ratio (FCR) and Protein efficiencyratio (PER) of rohu fingerings fed with 23% protein diets decreased while those ofthe fish fed with 28.5% protein diets increased as the dietary energy increased. Areduction of dietary protein level from 34% for rohu fingerlings to 29% or 23%could be obtained by providing a balanced P/E ratio in the diets, thus nearly 30 to50% of dietary protein could be spared. The protein sparing ability was noticed inthe fish by utilizing corn meal (35-41%)) in the diet. Among the other carbohydrateingredients tested for rohu, rice scrap and corn meal were well digested interms of dry matter (84.6% and 68.4%) total energy (81.6% and 72.6%), carbohydrate(84.5% and 79.6%) and protein digestive coefficients (87.4% and 78.2%).Sweet potato was very poorly digested by rohu fingerlings.